The Use of Learning Strategies during the COVID-19 Pandemic in Efforts to Improve Learning Outcomes of Elementary School Students - Sintia Kazelia Jaya; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
This study discusses the learning strategies used by elementary school teachers to students in instilling online learning in Muhammadiyah 1 Krian Elementary School. This needs to be researched, because learning strategies are one of the important aspects in giving birth to the character of students who are intelligent, creative and have character. The purpose of holding a learning strategy is to realize effectiveness and efficiency in teaching and learning activities. Strategy is a pattern that is deliberately planned and determined to carry out an action. The strategy also includes the objectives of the activity, the students involved in learning, the content of the activity, the process of the activity, and the infrastructure that supports learning activities. With the appropriate learning strategies during the COVID-19 pandemic, it is hoped that it can improve the ability of students, especially at SD Muhammadiyah 1 Krian to participate in a quality teaching process, where learning will provide opportunities for participants to ask questions, discuss, and actively use new knowledge gained and easy to understand. The formulation of the problem raised in this study is how the learning strategies applied by SD Muhammadiyah 1 Krian teachers will depend on the approach used, while how to implement the strategy can be determined through various learning methods. The existence of this learning strategy will affect the learning outcomes of the students themselves. The conclusion is that with the learning outcomes students are expected to be able to achieve a result that has been achieved after experiencing the learning process with their environment to obtain knowledge that is in accordance with the learning objectives.